Testing for Serial Correlation in Regression Models with Lagged Dependent Variables - Rayner, Robert K. (The Review of Economics and Statistics, 1993)
Bootstrap methods are investigated for approximating critical points to several widely used tests of serial correlation in regression models with lagged dependent variables. Simulation results suggest that the bootstrap accurately estimates the null distributions of the tests, in contrast to conventional approximations. Results of some studies on the size-adjusted power of the tests are also reported.